Comparison of Wide-Awake Local Anaesthesia without Tourniquet (WALANT) and Infraclavicular Brachial Plexus Block in the Plating of Distal Radius Fractures - Torun, Ömer; Aydın, Erbil; Çevik, Hüseyin Bilgehan (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2025)
We hypothesised that the WALANT technique can be consistently replicated and does not demand a high level of skill, and it leads to a higher patient satisfaction rate, improved clinical outcomes, and shorter waiting times compared with an IC-BP block.Forty-eight patients with isolated closed DRF were randomly assigned to the WALANT or IC-BP group. Demographic data, fracture classification, suitability for surgery, preoperative pain scores, and waiting times were collected prospectively. Perioperative parameters, clinical outcomes (pain scores, Disabilities of the Arm, Shoulder and Hand [DASH] scores), complications, patient satisfaction (Visual Analogue Patient Satisfaction [VAPS] scale), and return to work were assessed.Patients in the WALANT group had significantly shorter waiting times for surgery and postoperative hospital stays than the IC-BP group. No significant difference was found in intraoperative blood loss. The WALANT group had lower pain scores at postoperative weeks 2, 6, and 12. DASH scores improved over time in both groups, with the WALANT group having a significantly lower mean score during the follow-up period. Patients in the WALANT group returned to work earlier, and patient satisfaction was significantly higher.Compared with IC-BP blockade, the WALANT technique offers several advantages in DRF surgery, including shorter waiting times, shorter postoperative hospital stays, lower pain scores, better functional outcomes, faster return to work, and higher patient satisfaction. The WALANT technique offers a safe and effective alternative that eliminates the need for general anaesthesia or tourniquet application. This technique is suitable for DRF surgery because it provides consistent results and does not require a high level of expertise. Further studies with larger sample sizes are needed to confirm these results and investigate long-term outcomes.
Keywords: distal radius fracture; WALANT; wide-awake local anaesthesia; tourniquet; epinephrine; lidocaine